Water shutoff agent and application thereof in temperature resistance and / or salt resistance
By using a water-blocking agent composed of acrylamide and other components in carbonate reservoirs, a multi-interpenetrating network structure is formed, which solves the problem of poor sealing effect of existing water-blocking agents in high-temperature and high-salinity environments and achieves high-strength and long-term sealing effect.
Patent Information
- Application Number
- CN202411085128.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-08
- Publication Date
- 2026-02-10
AI Technical Summary
Existing water-blocking agents are difficult to effectively seal in high-temperature, high-salinity carbonate reservoirs for extended periods, and also suffer from insufficient temperature and salt resistance.
A water-blocking agent composed of acrylamide, vinyl sulfonate, modified starch, nano silica, crosslinking agent and water is used to form a multi-layer interpenetrating network structure through an in-situ underground crosslinking reaction, thereby improving the temperature and salt resistance of the gel.
It achieves long-term, high-strength sealing in high-temperature, high-mineralization environments, exhibits excellent temperature and salt resistance, and is suitable for water plugging needs in high-pressure formations.
Smart Images

Figure BDA0004984965380000091
Abstract
Description
Technical Field
[0001] This invention relates to the field of petroleum development, and in particular to a water-blocking agent. Background Technology
[0002] Carbonate reservoirs account for approximately 52% of the world's oil reserves and 60% of global oil and gas production. These reservoirs have good physical properties, are mainly fractured reservoirs, and have high oil production.
[0003] The Tarim Oilfield is located on the southwestern slope of the Akekule Uplift in the Shaya Uplift of the Tarim Basin. It is a large marine sedimentary carbonate oil reservoir formed by multiple phases of tectonic karstification on a large ancient uplift. It is the largest fracture-vuggy carbonate oilfield discovered in my country, with reservoir depths ranging from 5200 to 6500 m, reservoir temperatures from 130 to 165℃, and a maximum salinity of 24 × 10⁻⁶ m. 4 The concentration of mg / L indicates a low-permeability fractured reservoir. The Tahe Oilfield reservoirs are mainly distributed in the Ordovician system. Influenced by multiple tectonic movements, karstification, and diagenesis, a highly heterogeneous fracture and cave system has formed within the carbonate rocks. The scale and morphology of these fractures and caves are highly uncertain, exhibiting extreme heterogeneity. Caves are the primary reservoir spaces, while fractures and faults are the main connecting channels. Oil, gas, and water flow within these fractures and caves exhibits three modes: pipe flow, cavity flow, and seepage. Breakthroughs of edge and bottom water easily create dominant channels, causing a rapid increase in water cut in oil wells and shielding the remaining oil. The oil-water relationship in the reservoir is extremely complex, with localized sealed water and active, strong bottom water. Since the start of rolling development, water has been encountered in oil wells early on, and the water cut in the block has increased rapidly. Due to the high intensity of early extraction, water coning and water channeling have become increasingly serious. Methods such as shut-in, nozzle reduction, and water injection with cone pressure have become ineffective to varying degrees. Water shut-off has gradually become the main method for controlling water and increasing oil production in the oilfield, playing an increasingly important role.
[0004] Chemical water shut-off technology is a relatively economical and practical method. It involves using a water-shutting agent to seal high-permeability layers and large pores, reducing water absorption, increasing injection pressure, and forcing the displacing fluid into low-permeability layers. This improves the sweep efficiency, enhances waterflooding performance, and increases oilfield recovery. Consequently, various water-shutting chemicals have been developed. Classified by morphology, these agents can be categorized into three types: granular, cement-based, and gel-based.
[0005] Particulate plugging agents are mainly divided into two types: flexible particles and slowly expanding particles. Flexible particles are viscoelastic and adhere to each other in the formation through chemical reactions, blocking dominant formation channels and improving sweep efficiency, thereby enhancing oil recovery. Simultaneously, they can undergo elastic deformation in high-pressure formations, are not easily broken, and can migrate to deeper formations through fractures of different sizes for plugging. Slowly expanding particles expand upon contact with water in the formation, thereby plugging the target layer to improve reservoir heterogeneity and increase sweep efficiency. Both types of plugging agents are prepared on the surface, avoiding the influence of formation conditions on the system reaction. Particles of different sizes can be obtained through drying, grinding, and screening. However, the compatibility of the particle size with the pore-throat ratio of formation fractures is difficult to control. Because they are easily broken in high-pressure formations, their expansion ratio is limited in high-temperature, high-mineralization formations, and they quickly lose water, shrink, and harden, making long-term plugging difficult.
[0006] Cement-based plugging agents offer advantages such as high plugging strength, low cost, good temperature and salt resistance, and erosion resistance. They also have good resistance to negative pressure generated by near-wellbore operations. However, they also have drawbacks, including poor suspension, difficulty in migrating to deeper formations, and the tendency for injected water to bypass the formation after setting, shortening the waterdrive effect time. Because water-based cement lacks oil-water selectivity, it poses certain safety hazards during construction and is prone to accidents. Furthermore, due to the relatively large cement particles, it can only plug large pores and high-permeability layers in the reservoir, making it difficult to migrate to medium- and low-permeability formations, thus presenting challenges for plugging such formations. Oil-based cement plugging agents have weak oil-water selectivity, and their fluidity changes significantly when they encounter even a small amount of water during injection into the formation. This can block water-producing layers while also hindering oil migration within the formation, thus damaging the reservoir. Ultrafine cement and micro-particle cement, due to their smaller particle size, have better fluidity and penetration, allowing them to migrate into medium- to low-permeability formations and create plugs. However, the small particle size of ultrafine cement leads to an increased specific surface area, faster hydration, and shorter initial setting time, making it difficult to control the application time.
[0007] Gel-based plugging agents are a type of plugging agent that primarily uses physical blocking, supplemented by kinetic trapping and adsorption. Through the reaction of crosslinking agents and polymers, a product with a dense network structure is generated, forming a gel in the formation and creating physical blockage. This prevents water flow in dominant channels, forcing fluid flow to change direction and improving the water drive sweep efficiency. Polymer gel systems typically consist of water-soluble polymers or monomers, crosslinking agents, and other auxiliary reagents. Polymer gel plugging agents are generally classified into two types: The first type is called matured gel, similar to particulate plugging agents, which undergoes crosslinking before injection, dehydration, and then injection into the formation. The second type is called unmatured gel (in-situ crosslinked gel, also known as subsurface crosslinked plugging agent). This refers to an injected gel solution or "gelling agent" that is pumped into the target area and, after a certain maturation time, forms a three-dimensional (3D) network structure in the porous medium, acting as a flow-direction transfer or blocking agent. This system has low initial viscosity and good injection performance, but gel formation is easily affected by shear force, adsorption, reservoir environment, dilution, dispersion, and diffusion.
[0008] Among various plugging agents, granular plugging agents gel at the surface, avoiding the influence of the formation environment. However, the compatibility of particle size with the pore-throat ratio of formation fractures is difficult to control. Cement-based plugging agents have high sealing strength, low price, good temperature and salt resistance, and erosion resistance, but poor suspension, difficulty in transferring to deeper formations, and tendency for injected water to bypass the formation after solidification, shortening the water drive effect time, and lack of selectivity. Subsurface crosslinking plugging agents have the advantages of viscoelasticity, easy injection, strong controllability, and certain oil-water selectivity, but poor temperature and salt resistance and insufficient mechanical strength. Subsurface crosslinking plugging agents can compensate for the shortcomings of granular and cement-based plugging agents due to their low cost, easy pumping, easy penetration, and strong operability. However, the testing temperature is only around 100℃, and they generally have low temperature and salt resistance. At high temperatures, the gel strength is low or unable to gel. When exposed to high temperatures for a long time, the molecular chains inside the gel are prone to breakage, and the spatial network structure is prone to collapse, leading to a decline in the overall performance of the gel and thus losing the sealing effect. In addition, water-based polymer gel plugging agents are easily diluted by water when they enter large-scale fractured reservoirs. The dilution by formation water causes changes in the composition of the cross-linked system, which leads to a decrease in the gel strength of the plugging agent or even failure to gel, resulting in insufficient mechanical strength and affecting the water plugging effect. Summary of the Invention
[0009] One aspect of the present invention provides a water-blocking agent comprising acrylamide, vinyl sulfonate, modified starch, thickener, nano-silica, crosslinking agent and water.
[0010] In one specific embodiment, the vinyl sulfonate is sodium vinyl sulfonate.
[0011] In one specific embodiment, the modified starch is SAF-type modified starch and / or MSAF-type modified starch.
[0012] In one specific embodiment, the thickener is at least one of carrageenan, guar gum, and xanthan gum.
[0013] In one specific embodiment, the average particle size of the nano-silica is 30 to 100 nanometers.
[0014] In one specific embodiment, the crosslinking agent is N,N-methylenebisacrylamide.
[0015] In one specific embodiment, based on the mass of the water, there are 100 parts by mass of acrylamide, 12 to 20 parts by mass of vinyl sulfonate, 4 to 6 parts by mass of modified starch, 1 to 2 parts by mass of thickener, 1.5 to 2 parts by mass of nano silica, and 0.02 to 0.05 parts by mass of crosslinking agent.
[0016] The second invention provides the application of the water-blocking agent according to any one of the inventions in water-blocking and temperature / / or salt resistance in oilfields.
[0017] The beneficial effects of this invention are:
[0018] (1) The water-blocking agent of the present invention is an underground cross-linked water-blocking agent. After the water-blocking agent is prepared into a solution, it is pumped into the formation and undergoes an in-situ polymerization reaction underground. Compared with the preparation of granular water-blocking agents by processes such as polymerization, drying, granulation, and sieving on the ground (large particles cannot enter conventional porous media, and small particles cannot form effective seals in cracks and large pores), the underground cross-linked water-blocking agent does not have the problem of matching particle size with the size of formation cracks; the underground cross-linked water-blocking agent of the present invention does not have the problem of poor suspension of cement-based water-blocking agents; the preparation of the water-blocking agent of the present invention is simple.
[0019] (2) The water-blocking agent of this invention uses acrylamide monomer as the main agent, serving as the main component and structural support; N,N-methylenebisacrylamide is used as a crosslinking agent, providing three-dimensional crosslinking network connection points; sulfonate is an ionic functional group with the best temperature resistance performance enhancement, and the addition of the temperature-resistant monomer sodium vinyl sulfonate improves the temperature resistance of the plugging agent; modified starch, nano silica and thickener are added to form an interpenetrating structure with the acrylamide crosslinking network, improving the gel strength of the water-blocking agent for long-term sealing. Compared with existing underground crosslinking plugging agents, the multi-interpenetrating structure gel of the water-blocking agent of this invention can achieve high-strength water blocking with a mineralization resistance of up to 218,000 mg / L, a high temperature resistance of up to 130℃, and a gel storage modulus greater than 1000 Pa after long-term sealing. It has the characteristics of being resistant to higher temperatures and salinity, and has broad engineering application value and scientific research value.
[0020] (3) The water plugging agent of the present invention has added a thickener, which increases the initial viscosity of the water plugging agent to 800 mPa·s to 1200 mPa·s, ensuring the dilution resistance of the initial gel solution after it is transported to the formation environment. Compared with the existing underground cross-linking plugging agents, the water plugging agent of the present invention has good temperature and salt resistance. After temperature and salt resistance tests, the storage modulus of the plugging agent is greater than 1000 Pa. Detailed Implementation
[0021] The present invention will be further described below with reference to the embodiments. However, the embodiments of the present invention are merely illustrative examples and should not be construed as limiting the present invention under any circumstances.
[0022] Example 1
[0023] Preparation of Mixture A: Take 50g of water, add 12g of acrylamide and 4g of sodium vinyl sulfonate in sequence, stir at 200 rpm until homogeneous, then adjust the speed to above 500 rpm to form a vortex in the solution, add 1g of SAF modified starch (Dezhou Runde Starch Co., Ltd.), stir for 1 hour to completely dissolve the SAF modified starch, and obtain Mixture A;
[0024] Preparation of Mixture B: Take 50g of water, adjust the speed to more than 500 rpm to form a vortex in the solution, add 1.5g of carrageenan, stir evenly, then add 1g of nano-silica with an average particle size of 30nm, stir for 1h to obtain Mixture B;
[0025] Preparation of water-blocking agent: Pour mixture A into mixture B, mix evenly, add 0.02g N,N-methylenebisacrylamide, stir evenly, and the water-blocking agent is obtained.
[0026] Two 50ml portions of the water-blocking agent were taken and placed in a 100ml reactor liner. The mixture was reacted at 130℃ for 1 hour to form a gel. The storage modulus, loss modulus, and loss angle of one portion after 1 hour of gelation were measured. For the other portion, 50ml of simulated formation brine with a salinity of 218000mg / L was added to the reactor liner, and the reactor was aged in a 130℃ oven for 30 days. The storage modulus, loss modulus, and loss angle were then measured. The specific measurements are as follows.
[0027] The measurements were performed using a dynamic thermomechanical analyzer. The test sample was a cylinder with a diameter of 12 mm and a height of 7 mm. The test frequency was 1 Hz, and the test time was 200 s. The storage modulus characterizes the elasticity of the sample, while the loss modulus characterizes the viscosity. If the storage modulus is greater than the loss modulus, the gel behaves as an elastic solid; otherwise, it is a viscous liquid. The loss angle δ characterizes the strength of viscoelasticity. If the sample δ < 45°, elasticity dominates, and the sample has a solid-like structure, indicating a viscoelastic solid. The smaller the δ, the stronger the elasticity. If the gel δ > 45°, viscosity dominates, and the sample is a viscoelastic liquid. The larger the δ, the weaker the elasticity.
[0028] The results are shown in Table 1.
[0029] Example 2
[0030] Preparation of Mixture A: Take 50g of water, add 20g of acrylamide and 6g of sodium vinyl sulfonate in sequence, stir at 200 rpm until homogeneous, then adjust the speed to above 500 rpm to form a vortex in the solution, add 2g of saf-type modified starch, stir for 1 hour to completely dissolve the saf-type modified starch, and obtain Mixture A.
[0031] Preparation of Mixture B: Take 50g of water, adjust the speed to more than 500 rpm to form a vortex in the solution, add 2g of carrageenan, stir evenly, then add 2g of silica with an average particle size of 30nm, stir for 1h to obtain Mixture B.
[0032] Preparation of water-blocking agent: Pour mixture A into mixture B, mix evenly, add 0.05g N,N-methylenebisacrylamide, stir evenly, and the water-blocking agent is obtained.
[0033] Two 50ml portions of the water-blocking agent were taken and placed in a 100ml reactor liner. The mixture was reacted at 130℃ for 1 hour to form a gel. The storage modulus, loss modulus, and loss angle of one portion after 1 hour of gelation were measured. For the other portion, 50ml of simulated formation brine with a salinity of 218000mg / L was added to the reactor liner, and the reactor was aged in a 130℃ oven for 30 days. The storage modulus, loss modulus, and loss angle were then measured. The specific measurements are as follows.
[0034] The measurements were performed using a dynamic thermomechanical analyzer. The test sample was a cylinder with a diameter of 12 mm and a height of 7 mm. The test frequency was 1 Hz, and the test time was 200 s. The storage modulus characterizes the elasticity of the sample, while the loss modulus characterizes the viscosity. If the storage modulus is greater than the loss modulus, the gel behaves as an elastic solid; otherwise, it is a viscous liquid. The loss angle δ characterizes the strength of viscoelasticity. If the sample δ < 45°, elasticity dominates, and the sample has a solid-like structure, indicating a viscoelastic solid. The smaller the δ, the stronger the elasticity. If the gel δ > 45°, viscosity dominates, and the sample is a viscoelastic liquid. The larger the δ, the weaker the elasticity.
[0035] The results are shown in Table 1.
[0036] Example 3
[0037] The preparation process is the same as in Example 1, except that 1.5g of carrageenan in mixture B is replaced with 1.5g of guar gum, and the final water-blocking agent is obtained.
[0038] The performance of the water-blocking agent prepared in this embodiment was tested:
[0039] Two 50ml portions of the water-blocking agent were taken and placed in a 100ml reactor liner. The mixture was reacted at 130℃ for 1 hour to form a gel. The storage modulus, loss modulus, and loss angle of one portion after 1 hour of gelation were measured. For the other portion, 50ml of simulated formation brine with a salinity of 218000mg / L was added to the reactor liner, and the reactor was aged in a 130℃ oven for 30 days. The storage modulus, loss modulus, and loss angle were then measured. The specific measurements are as follows.
[0040] The measurements were performed using a dynamic thermomechanical analyzer. The test sample was a cylinder with a diameter of 12 mm and a height of 7 mm. The test frequency was 1 Hz, and the test time was 200 s. The storage modulus characterizes the elasticity of the sample, while the loss modulus characterizes the viscosity. If the storage modulus is greater than the loss modulus, the gel behaves as an elastic solid; otherwise, it is a viscous liquid. The loss angle δ characterizes the strength of viscoelasticity. If the sample δ < 45°, elasticity dominates, and the sample has a solid-like structure, indicating a viscoelastic solid. The smaller the δ, the stronger the elasticity. If the gel δ > 45°, viscosity dominates, and the sample is a viscoelastic liquid. The larger the δ, the weaker the elasticity.
[0041] The results are shown in Table 1.
[0042] Example 4
[0043] The preparation process is the same as in Example 1, except that 1.5g of carrageenan in mixture B is replaced with 1.5g of xanthan gum, and the final water-blocking agent is obtained.
[0044] Two 50ml portions of the water-blocking agent were taken and placed in a 100ml reactor liner. The mixture was reacted at 130℃ for 1 hour to form a gel. The storage modulus, loss modulus, and loss angle of one portion after 1 hour of gelation were measured. For the other portion, 50ml of simulated formation brine with a salinity of 218000mg / L was added to the reactor liner, and the reactor was aged in a 130℃ oven for 30 days. The storage modulus, loss modulus, and loss angle were then measured. The specific measurements are as follows.
[0045] The measurements were performed using a dynamic thermomechanical analyzer. The test sample was a cylinder with a diameter of 12 mm and a height of 7 mm. The test frequency was 1 Hz, and the test time was 200 s. The storage modulus characterizes the elasticity of the sample, while the loss modulus characterizes the viscosity. If the storage modulus is greater than the loss modulus, the gel behaves as an elastic solid; otherwise, it is a viscous liquid. The loss angle δ characterizes the strength of viscoelasticity. If the sample δ < 45°, elasticity dominates, and the sample has a solid-like structure, indicating a viscoelastic solid. The smaller the δ, the stronger the elasticity. If the gel δ > 45°, viscosity dominates, and the sample is a viscoelastic liquid. The larger the δ, the weaker the elasticity.
[0046] The results are shown in Table 1.
[0047] Example 5
[0048] The preparation process is the same as in Example 1, except that 1g of silica with an average particle size of 30nm in mixture B is replaced with 1g of silica with an average particle size of 100nm, and the water-blocking agent is finally obtained.
[0049] Two 50ml portions of the water-blocking agent were taken and placed in a 100ml reactor liner. The mixture was reacted at 130℃ for 1 hour to form a gel. The storage modulus, loss modulus, and loss angle of one portion after 1 hour of gelation were measured. For the other portion, 50ml of simulated formation brine with a salinity of 218000mg / L was added to the reactor liner, and the reactor was aged in a 130℃ oven for 30 days. The storage modulus, loss modulus, and loss angle were then measured. The specific measurements are as follows.
[0050] The measurements were performed using a dynamic thermomechanical analyzer. The test sample was a cylinder with a diameter of 12 mm and a height of 7 mm. The test frequency was 1 Hz, and the test time was 200 s. The storage modulus characterizes the elasticity of the sample, while the loss modulus characterizes the viscosity. If the storage modulus is greater than the loss modulus, the gel behaves as an elastic solid; otherwise, it is a viscous liquid. The loss angle δ characterizes the strength of viscoelasticity. If the sample δ < 45°, elasticity dominates, and the sample has a solid-like structure, indicating a viscoelastic solid. The smaller the δ, the stronger the elasticity. If the gel δ > 45°, viscosity dominates, and the sample is a viscoelastic liquid. The larger the δ, the weaker the elasticity.
[0051] The results are shown in Table 1.
[0052] Example 6
[0053] The preparation process is the same as in Example 1, except that 1g of saf-type modified starch in mixture A is replaced with 1g of msaf-type modified starch (Dezhou Runde Starch Co., Ltd.), and the water-blocking agent is finally obtained.
[0054] Two 50ml portions of the water-blocking agent were taken and placed in a 100ml reactor liner. The mixture was reacted at 130℃ for 1 hour to form a gel. The storage modulus, loss modulus, and loss angle of one portion after 1 hour of gelation were measured. For the other portion, 50ml of simulated formation brine with a salinity of 218000mg / L was added to the reactor liner, and the reactor was aged in a 130℃ oven for 30 days. The storage modulus, loss modulus, and loss angle were then measured. The specific measurements are as follows.
[0055] The measurements were performed using a dynamic thermomechanical analyzer. The test sample was a cylinder with a diameter of 12 mm and a height of 7 mm. The test frequency was 1 Hz, and the test time was 200 s. The storage modulus characterizes the elasticity of the sample, while the loss modulus characterizes the viscosity. If the storage modulus is greater than the loss modulus, the gel behaves as an elastic solid; otherwise, it is a viscous liquid. The loss angle δ characterizes the strength of viscoelasticity. If the sample δ < 45°, elasticity dominates, and the sample has a solid-like structure, indicating a viscoelastic solid. The smaller the δ, the stronger the elasticity. If the gel δ > 45°, viscosity dominates, and the sample is a viscoelastic liquid. The larger the δ, the weaker the elasticity.
[0056] The results are shown in Table 1.
[0057] Comparative Example 1
[0058] Compared with Example 1, a water-blocking agent was prepared by adding only 12g of acrylamide, 4g of sodium vinyl sulfonate, and 0.02g of N,N-methylenebisacrylamide to 100g of clean water, while keeping other conditions unchanged.
[0059] 50 ml of water-blocking agent was placed in a 100 ml reactor liner and reacted at 130 °C for 1 hour to form a gel. 50 ml of simulated formation brine with a mineralization of 218,000 mg / L was added to the reactor liner, and the reactor was placed in a 130 °C oven for aging. On the 9th day of aging, the water-blocking agent was completely destroyed and changed from a solid to a low-viscosity liquid.
[0060] Comparative Example 2
[0061] Compared with Example 1, a water-blocking agent was prepared by adding only 12g of acrylamide, 4g of sodium vinyl sulfonate, 1.5g of carrageenan, and 0.02g of N,N-methylenebisacrylamide to 100g of clean water, while keeping other conditions unchanged.
[0062] Two 50ml portions of the water-blocking agent were taken and placed in a 100ml reactor liner. The mixture was reacted at 130℃ for 1 hour to form a gel. The storage modulus, loss modulus, and loss angle of one portion after 1 hour of gelation were measured. For the other portion, 50ml of simulated formation brine with a salinity of 218000mg / L was added to the reactor liner, and the reactor was aged in a 130℃ oven for 30 days. The storage modulus, loss modulus, and loss angle were then measured. The specific measurements are as follows.
[0063] The measurements were performed using a dynamic thermomechanical analyzer. The test sample was a cylinder with a diameter of 12 mm and a height of 7 mm. The test frequency was 1 Hz, and the test time was 200 s. The storage modulus characterizes the elasticity of the sample, while the loss modulus characterizes the viscosity. If the storage modulus is greater than the loss modulus, the gel behaves as an elastic solid; otherwise, it is a viscous liquid. The loss angle δ characterizes the strength of viscoelasticity. If the sample δ < 45°, elasticity dominates, and the sample has a solid-like structure, indicating a viscoelastic solid. The smaller the δ, the stronger the elasticity. If the gel δ > 45°, viscosity dominates, and the sample is a viscoelastic liquid. The larger the δ, the weaker the elasticity.
[0064] The results are shown in Table 1.
[0065] Table 1 shows that the gels formed after reacting at 130℃ for 1 hour in Examples 1 to 6 exhibit high storage modulus and loss modulus, indicating good viscoelasticity. The storage modulus is greater than the loss modulus, indicating that the gels exhibit solid properties. After aging at 130℃ for 30 days in Examples 1 to 6, the gel structure changed due to the high temperature and high salt environment, resulting in varying degrees of decrease in both storage modulus and loss modulus, indicating reduced viscoelasticity. Comparing the loss angles of the gels from Examples 1 to 6 after reacting at 130℃ for 1 hour and aging at 130℃ for 30 days shows that the loss angle increased, indicating decreased elasticity and increased viscosity. However, the storage modulus is greater than the loss modulus, indicating that the gels exhibit solid properties. In Comparative Example 2, the storage modulus and loss modulus of the gel decreased significantly after aging at 130℃ for 30 days. Compared to the comparative example, Examples 1 to 6 show significant improvement.
[0066] Table 1
[0067]
[0068] Furthermore, compared to Example 1, Comparative Example 1 only formed a single cross-linked polyacrylamide network. Compared to Example 1, which contained a cross-linked polyacrylamide network, a dual natural polymer reinforcing network, and a nano-silica interpenetrating network, its temperature and salt resistance was significantly reduced. Compared to Example 1, Comparative Example 2 formed both a single cross-linked polyacrylamide network and a single natural polymer reinforcing network. Compared to Example 1, which contained a cross-linked polyacrylamide network, a dual natural polymer reinforcing network, and a nano-silica interpenetrating network, after temperature and salt resistance, although the gel had a certain degree of viscoelasticity, its appearance collapsed and its shape retention time was not as good as that of Example 1.
[0069] While the present invention has been described with reference to specific embodiments, those skilled in the art will understand that various changes can be made without departing from the true spirit and scope of the invention. Furthermore, numerous modifications can be made to the subject, spirit, and scope of the invention to suit specific situations, materials, material compositions, and methods. All such modifications are included within the scope of the claims of the present invention.
Claims
1. A water-blocking agent comprising acrylamide, vinyl sulfonate, modified starch, thickener, nano-silica, crosslinking agent and water.
2. The water-blocking agent according to claim 1, characterized in that, The vinyl sulfonate is sodium vinyl sulfonate.
3. The water-blocking agent according to claim 1, characterized in that, The modified starch is saf-type modified starch and / or msaf-type modified starch.
4. The water-blocking agent according to claim 1, characterized in that, The thickener is at least one of carrageenan, guar gum, and xanthan gum.
5. The water-blocking agent according to claim 1, characterized in that, The average particle size of nano-silica is 30 to 100 nanometers.
6. The water-blocking agent according to claim 1, characterized in that, The crosslinking agent is N,N-methylenebisacrylamide.
7. The water-blocking agent according to any one of claims 1 to 6, characterized in that, The mixture comprises 100 parts by weight of water, 12 to 20 parts by weight of acrylamide, 4 to 6 parts by weight of vinyl sulfonate, 1 to 2 parts by weight of modified starch, 1.5 to 2 parts by weight of thickener, 1 to 2 parts by weight of nano silica, and 0.02 to 0.05 parts by weight of crosslinking agent.
8. The application of the water shut-off agent according to any one of claims 1 to 7 in water shut-off in oilfields with high temperature and / or salt resistance.